A Geographical Study of Indian Geography in the Eyes of Geographers: Evolution of Geographical Studies in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Geography as a discipline, in India, has the processes of liberalization, privatization and globalization have left its imprint on the persona of geography and its identity, image and relevance are being debated at various forum. In the last 24 years since NAGI has made its appearance there are roughly around 15 presidential addresses focusing on relevance of the subject, its role in making of the society, area of strengths and weaknesses and role of geographers in the nation building endeavour. Within this background purpose of the paper is not to evaluate anyone’s scholarly contribution in the field of geography but to highlight and critically examine the changing views of the geographers of two generations the one focusing on contents, methods and techniques and the other showing concerns about identity, image and space of the discipline in the academic world.